Kajian kecenderungan antenatal care di Kota Bitung Sulawesi Utara periode 2015-2017 - Anjani, Grace Sophie; Siagian, Iyone E. T.; Kuhon, Frelly V. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2018)
Background: The goal of Antenatal care (ANC) is to prepare for birth and as well as prevent, detect, alleviate, or to manage the health problems during pregnancy that affect mothers and the babies. Approximately 830 women die everyday around the world because of complication related pregnancy or labour with preventable causes. In 2015 maternal mortality rate in Indonesia was 305 deaths per 100.000 live births. Aim: To describe the tendency of pregnant women to go to antenatal care. Methods: This is a descriptive research with cross sectional design model and the data was taken from Health Profile of Bitung City from 2015-2017. Results: There was an increase of K-1 visit about 3,3% and an increase of K-4 visit about 0,1%. The coverage of Fe1 decrease about 1,24% and supplementation of Fe3 decrease about 0,19%. TT1 vaccination increase about 14% and 8% for TT2. Conclusion: The tendency of pregnant women to make K-1 and K-4 pregnancy visits is quite high. Meanwhile, the tendency of pregnant women to get iron (Fe) 1 tablets is quite high, while Fe3 is slightly lower and the tendency to immunize Tetanus toxoid (TT) in Bitung City is still relatively low.